(untitled) (Tempo e Argumento, 2022)
At the end of the 1980s, the National Foundation for Minors’ Welfare - Funabem published the Meninas da Vida report, which aimed to debate the assistance to street girls. Based on a prescriptive logic, with the objective of circulating nationally, the document provided recommendations for the so-called social educators, who, for the authorship of the report, were the agents responsible for the socio-pedagogical care of these girls. In this context, this article aims to analyze the discourse of the strategies presented for assisting girls in this report, problematizing the concept of “girls of life” and the “arts of governing” street children and adolescents. It is noteworthy that this period was marked by the effervescence of re-democratization, from which emerged the National Movement of Street Boys and Girls, which questioned legislation and policies based on the logic of “minors’ welfare”, bringing a pedagogical proposal to recognize these girls as protagonists of their stories. In this way, it is intended to put on screen how the relations between Funabem and the Movement were produced, highlighting, beyond the fissures, how the issue of the girl/woman came to be recognized as a problem of social policy, given that even the At the end of the 1970s, most of the policies produced by the State were marked by the “erasing” of the status of the girl-woman, classifying them generically as “minors”.